Accounting for the gender gap in adolescents’ life satisfaction: evidence from nationally representative samples of school attendees in Luxembourg - Romain Brisson; Felipe G. Mendes; Carolina Catunda (International Journal of Adolescence and Youth, 2023)
ABSTRACTResearch on gender differences in adolescents’ life satisfaction has reported inconsistent findings to date. The present study aimed to (a) ascertain whether a gender gap in life satisfaction exists in Luxembourg, (b) estimate the predictive power of gender when controlling for well-identified predictors of life satisfaction, and (c) assess potential gender differences in our predictors’ influence on life satisfaction. We used data from 2006 to 2022 pertaining to nationally representative samples of school attendees in Luxembourg (n = 46,937) to achieve our first research goal. We relied on data collected in 2022 (n = 9,432) to achieve our two other research goals. We found boys to consistently report higher life satisfaction than girls over time. However, gender did not predict life satisfaction when controlling for our other predictors. Moreover, the influence of most of the examined factors on life satisfaction did not vary with gender.